How many procedures does it take? Success of a CVS training program for Maternal Fetal Medicine fellows†. (2nd December 2016) - Gimovsky, Alexis C.; Moreno, Sindy C.; Nicholas, Sara; Roman, Amanda; Weiner, Stuart
Abstract: Objectives: To quantify the learning curve for a training program for Maternal Fetal Medicine (MFM) fellows in obtaining successful transvaginal chorionic villus sampling (CVS) results in women with early pregnancy failure (EPF). Methods: Retrospective observational cohort study of transvaginal CVS and subsequent manual vacuum aspiration (MVA) performed by MFM fellows. CVS samples were sent for karyotype, and products of conception (POC) were sent if CVS sample did not yield a result. Success was defined as karyotype result on CVS specimen. Results: A total of 130 women with EPF up to 9 weeks of gestation underwent transvaginal CVS and MVA from December 2011 to April 2015. CVS samples were successful in 53 (40.8%) cases, POC were analyzed for karyotype in 68 (52.3%) cases, and maternal decidua was obtained in 9 (6.9%) cases. Nine MFM fellows performed the CVS and MVA procedures. The mean number of procedures per fellow was 14 (5–24). The average success rate of transvaginal CVS sample was 33.3% after the first procedure and 50% at the 14th procedure. One procedure was performed per patient. Conclusions: Success increased over time from 33.3% to 50.0%. Given the gestational age and failed pregnancy status, this is a reasonable success rate for CVS at time of EPF. © 2016 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Training MFM fellows on CVS is a clinical challenge and often requires simulation or training on non‐continuing pregnancies Fewer graduating MFM fellows have opportunities to train in CVS during fellowship What does this study adds? Our study adds quantitative evidence to support a training method for Maternal Fetal Medicine fellows in chorionic villus sampling